2017
DOI: 10.1111/echo.13704
|View full text |Cite
|
Sign up to set email alerts
|

Early anthracycline‐induced cardiotoxicity monitored by echocardiographic Doppler parameters combined with serum hs‐cTnT

Abstract: We demonstrated that echocardiographic PW Doppler-derived Tei index, and TDI-derived Sm, combined with serum hs-cTnT level can be obtained in outpatient settings to monitor early cardiac toxicity induced by anthracycline therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Finally, in the lack of consistent data, we strongly recommend clinicians to consider an integrated biomarker approach, combining circulating biomarkers with imaging methods. This combined technique showed indeed improved specificity, while sensitivity, as expected, dropped [9,33,34].…”
Section: Other Circulating Biomarkers In Cardio-oncologysupporting
confidence: 77%
See 1 more Smart Citation
“…Finally, in the lack of consistent data, we strongly recommend clinicians to consider an integrated biomarker approach, combining circulating biomarkers with imaging methods. This combined technique showed indeed improved specificity, while sensitivity, as expected, dropped [9,33,34].…”
Section: Other Circulating Biomarkers In Cardio-oncologysupporting
confidence: 77%
“…The predictive value of hs-cTn is consistent among other neoplasm patients as well. Zhang et al followed patients with B cell lymphoma receiving anthracyclines [33]. They have also reported a significant hs-cTn rise following anthracycline treatment.…”
Section: Cardiac Troponins Predictors Of Ctacmentioning
confidence: 99%
“…A number of foreign research results show that LVEF values were not significantly reduced when the average cumulative dose of anthracycline was up to 350-700 mg/m 2. [16][17][18] In our study, LVEF was significantly reduced when the cumulative dose of anthracycline was at 320 mg/m 2 . Previous studies on the sensitivity of GLS in monitoring anthracycline-induced myocardial damage showed that when the average cumulative dose was 60 mg/m 2 , GLS did not decrease significantly, 19 and when the average cumulative dose was 266 mg/m 2 (200-298 mg/m 2 ), GLS decreased significantly.…”
Section: Discussionsupporting
confidence: 47%
“…Some biomarkers [34][35][36] and decreased global longitudinal strain [37,38] have been reported to be useful in the early diagnosis of cardiotoxicity. Furthermore, early diagnosis and therapy for cardiotoxicity have been reported to be associated with better outcome [31][32][33].…”
Section: Discussionmentioning
confidence: 99%